A Pilot Trial Evaluating Zoledronic Acid Induced Changes in [(18)F]FMAU-Positron Emission Tomography Imaging of Bone Metastases in Prostate Cancer - Vaishampayan, Ulka N. (Mol Imaging Biol, 2017)
PURPOSE: We conducted a pilot trial utilizing [(18)F]FMAU [1-(2′-deoxy-2′-[(18)F]fluoro-β-d-arabinofuranosyl thymine] as a tumor tracer in positron emission tomography (PET) and evaluated its reproducibility, and changes in maximum and peak standardized uptake value (SUVmax and SUVpeak) with zoledronic acid treatment in castrate resistant prostate cancer (CRPC) patients with bone metastases (BM). PROCEDURES: Eligible patients had CRPC with radiographic evidence of BM and creatinine clearance >30 ml/min. Two baseline [(18)F]FMAU-PET scans (about 1 week apart, range 2–12 days) were obtained for testing reproducibility. Zoledronic acid 4 mg was infused over 15 min within 1 week after second scan and a third PET scan was obtained 7 days later. The bony lesion with the highest uptake on the first scan was compared with later scans. Bone turnover markers and prostate-specific antigen (PSA) were obtained pre- and post-therapy. PET response was defined as decline in SUVmean of ≥15 % after zoledronic acid. RESULTS: Eleven patients were evaluated, median age was 65 years, five were African-American and six were Caucasian, and median PSA level was 36.3 ng/ml (range 1.0–1209.3). Notably, the range of absolute percent SUVmax changes varied between 0.77 and 54.7, and only nine measurements were greater than one (1.09–2.19). Zoledronic acid did not appreciably change FMAU uptake. No clinical response was noted. Urine N-telopeptide (NTx) was markedly decreased in all patients after zoledronic acid and serum bone-specific alkaline phosphatase (BSAP) registered a modest change. Urine NTx correlated more closely with SUV max than serum BSAP. CONCLUSIONS: FMAU tracer was able to detect bone metastases in CRPC patients but uptake was highly variable in bony lesions. Zoledronic acid did not produce an appreciable change in scans. Future investigations of FMAU tracer as a marker of early response in CRPC is recommended.